In Situ Low-Temperature Chemical Bath Deposition of CdS Thin Films without Thickness Limitation: Structural and Optical Properties - Mouad Ouafi; Boujemaâ Jaber; Lahoucine Atourki; Najwa Zayyoun; Ahmed Ihlal; Ahmed Mzerd; Larbi Laânab (International Journal of Photoenergy)
In this work, thin CdS films have been deposited using the chemical bath deposition technique (CBD). Different synthesis parameters, such as number of runs, deposition time, and postannealing temperature, are studied and optimized in order to avoid the supersaturation phenomenon and to achieve a low-temperature growth. CdS thin films, of cubic structure, oriented along the (111) direction with homogenous and smooth surface, have been deposited by using the CBD growth process without any annealing treatment. Based on a set of experimental observations, we show that the solution saturation phenomenon can be avoided if the deposition is performed in several runs at a short deposition time. Throughout the CBD technique, it is then possible not only to overcome any film thickness limitation but also to grow the CdS films in a single technological step at a low temperature and without any postdeposition annealing treatment. CdS films with excellent structural quality and a controllable thickness are obtained when the deposition bath temperature is fixed at 65°C. In addition, deposited films exhibit an optical transmittance ranging from 70 to 95% depending on the synthesis parameters, with band gap energy around 2.42 eV. The process developed in this work might be useful for depositing CdS films on flexible substrates.